Epistemology and the social - Agazzi, Evandro.; Echeverría, Javier.; Gómez Rodríguez, Amparo. (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2008)
Epistemology had to come to terms with "the social" on two different occasions. The first was represented by the dispute about the epistemological status of the "social" sciences, and in this case the already well established epistemology of the natural sciences seemed to have the right to dictate the conditions for a discipline to be a science. But the social sciences could successfully vindicate the legitimacy of their specific criteria for scientificity. More recently, the impact of social factors on the construction of our knowledge (including scientific knowledge) has reversed, in a certain sense, the old position and promoted social inquiry to the role of a criterion for evaluating the purport of cognitive (including scientific) statements. But this has undermined the traditional characteristics of objectivity and rigor that seem constitutive of science. Moreover, in order to establish the real extent to which social conditionings have an impact on scientific knowledge one must credit sociology with a sound ground of reliability, and this is not possible without a preliminary "epistemological" assessment. These are some of the topics discussed in this book, both theoretically and with reference to concrete cases.